Analisis Potensi Pendapatan dan Kemandirian Daerah di Kawasan Arek Jawa Timur - Abdillah, Khubbi (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2024)
The study aims to determine the magnitude of the potential for regional income and independence arek region in East Java Province in 2017 – 2021, by calculating the Location Quotient analysis, the degree of fiscal decentralization, and the regional fiscal capacity index. The results of the LQ calculation show that Batu City has the highest LQ in other service sectors. Analysis of the highest degree of fiscal decentralization and regional fiscal capacity index is owned by Surabaya City. The research results recommend that local governments need to optimize their economic potential as a source of tax revenue, increase local own-source revenue (PAD) so that they’re not dependent on transfers from central government, and increase regional capabilities by expanding a new tax base to finance government spending.